2017
DOI: 10.1002/pola.28929
|View full text |Cite
|
Sign up to set email alerts
|

RAFT synthesis of polystyrene‐block‐poly(polyethylene glycol monomethyl ether acrylate) for zinc phthalocyanine‐loaded polymeric micelles as photodynamic therapy photosensitizers

Abstract: A series of polystyrene‐block‐poly(polyethylene glycol monomethyl ether acrylate) (PStm‐b‐PPEGAn) polymers were systematically synthesized as carriers for zinc phthalocyanine (ZnPc) for photodynamic therapy via reversible addition and fragmentation chain transfer polymerization. The degree of polymerization of the styrene (m) and PEGA units (n) of the resulting block copolymers were characterized to be n = 174, 40, and 18 for m = 52; and n = 200, 84, and 31 for m = 30. All the block copolymers formed micelles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…It means that the reactivity ratios of both monomers (r 1 and r 2 ) are lower than unity. There are numerous papers describing synthesis and investigation of block polymers consisting of styrene and PEG methacrylates [37,38] published in the literature; however, there are no publications describing RAFT copolymerization of such monomers. Despite this fact, the free radical polymerization of monomers with a similar structure was extensively studied earlier.…”
Section: Synthesis Of P(st-co-peo 5 Mema) Copolymersmentioning
confidence: 99%
“…It means that the reactivity ratios of both monomers (r 1 and r 2 ) are lower than unity. There are numerous papers describing synthesis and investigation of block polymers consisting of styrene and PEG methacrylates [37,38] published in the literature; however, there are no publications describing RAFT copolymerization of such monomers. Despite this fact, the free radical polymerization of monomers with a similar structure was extensively studied earlier.…”
Section: Synthesis Of P(st-co-peo 5 Mema) Copolymersmentioning
confidence: 99%
“…This can be expected because of the very low ZnPc concentration in comparison to that used in our previous study. 58 In contrast, ZnPc-loaded micelles of 1 exerted excellent photocytotoxicity under the same condition; almost complete annihilation was achieved upon photoirradiation of 20 J cm −2 with a ZnPc dose of only 0.05 μM.…”
Section: Resultsmentioning
confidence: 96%
“…56,57 Previously, we demonstrated the synthesis of polystyrene-bpoly(polyethylene glycol monomethyl ether acrylate) (PSt-b-PPEGA) and the preparation of ZnPc-loaded polymer micelles. 58 The efficiency of encapsulating ZnPc depended on the molecular architecture of PSt-b-PPEGA. Disappointingly, the photocytotoxicity of the resulting ZnPc-loaded polymer micelles was very low in HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Feuser et al [ 66 ] reported ZnPc loaded poly(methyl methacrylate) (PMMA) NPs as PDT agents for leukemia treatment. Obata et al reported a series of polystyrene- b -poly(polyethylene glycol monomethyl ether acrylate) (PSt- b -PPEGA) [ 67 ] and poly(N-substituted acrylamide)- b -poly(polyethylene glycol monomethyl ether acrylate) (P(R)- b -PPEGA) [ 68 ] copolymers synthesized via RAFT as nanocarriers for ZnPc for PDT. Both systems displayed the light-dose-dependent cytotoxicity of ZnPc-loaded micelles in cancer cells, suggesting a promising photodynamic effect for hydrophobic PS loaded in micelles.…”
Section: Phthalocyanine-polymeric Nanoparticle Delivery Systems For Cancer Photodynamic Therapymentioning
confidence: 99%